1997
DOI: 10.1177/105268469700700303
|View full text |Cite
|
Sign up to set email alerts
|

Restructuring Schools for Democracy: Principals’ Perspectives

Abstract: Currently there is renewed emphasis among theorists and practitioners on democratic schooling. Although frequently equated with school governance, democratic schooling extends beyond governance structures into all aspects of school and classroom practice. What democratic schooling means for the practices of principals, however, is unclear. In democratic schools principals not only no longer sit at the apex of the governance hierarchy but they must also discover what it means to be a democratic school in the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…Qualitative studies of democratic school communities and leaders mentioned trust more as a side note than as a core focus of study, if mentioned at all (Allen & Glickman, 1998;Blase & Blase, 2001;Blase et al, 1995;Cate et al, 2006;O'Hair & Reitzug, 1997;Rusch, 1998). Few studies explicitly linked democracy and trust, either through research questions or findings.…”
Section: Faculty Trust Explains Whymentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative studies of democratic school communities and leaders mentioned trust more as a side note than as a core focus of study, if mentioned at all (Allen & Glickman, 1998;Blase & Blase, 2001;Blase et al, 1995;Cate et al, 2006;O'Hair & Reitzug, 1997;Rusch, 1998). Few studies explicitly linked democracy and trust, either through research questions or findings.…”
Section: Faculty Trust Explains Whymentioning
confidence: 99%
“…(p. 96) In this case study, the school leader intentionally designed systems and processes that reflected democratic principles, and as the teachers engaged in their work in new ways, trust developed and student learning improved. In a qualitative study of school leaders who were recognized for their implementation of more democratic school reforms, O'Hair and Reitzug (1997) found three primary themes characterizing principal practice: expanding involvement in school decision making and discourse, focusing attention on connections, and promoting inquiry around core beliefs. Their description of principal practice again reflected the democratic principles in action but did not inquire into or report on the role or importance of trust in these schools.…”
Section: Faculty Trust Explains Whymentioning
confidence: 99%
“…However, no research studies so far have examined school principals' basic beliefs and values regarding the purposes of education and goals of schooling, and very few studies have focused on principals' own perceptions of school change and their special roles in reform. A current search in the ERIC database on the topic of educational leaders/school principals and school reform yields several hundred references, but only a few of them are based on qualitative data gathered from school principals themselves (see, for example, Hallinger, 1991;O'Hair & Reitzug, 1997;Trail, 2000). The comparative research study reported here will help fill this void and inform the public and policymakers of the unique perspectives and visions of school principals.…”
mentioning
confidence: 99%
“…Despite the variations, democratic schools need to ensure the existence of the following three structural features: democratic forms of school governance, classroom management, and human relations (Mosher, et al, 1994;O'Hair and Reitzug, 1997;Kira, 1999Kira, , 2004 5 . Democratic school governance takes the forms of direct democracy in a small school (or a small unit within a large school) in which every member is involved in shared decision making, as well as of representative democracy in a larger school in which representatives of students and staff make decisions.…”
Section: Philosophical Foundations and Structural Features Of Democramentioning
confidence: 99%